Assessment of the cluster potential of the Muscovado Industry in Negros Oriental - Arbon, Gilbert R.; Posadas, Roger D. (Quezon City University of the Philippines Diliman, 2012)
Negros Oriental leads in sugarcane production in the Central Visayas Region. Yet dependence on the traditional sugar industry, with its vast plantations and sugar centrals, may partly account for the lingering underdevelopment of the province-the industry has been static for a long time. The status quo changed when muscovado mills started proliferating in 2007, reaching a total of seven. Two later closed, leaving five firms in competition. Three of them are small/medium-sized corporations, one is a small-sized cooperative, and one is a micro-sized single proprietorship. Their aggregate investment has exceeded P48 million. About 90 percent of this amount came from their equity; the rest came from government assistance. The corporations are availing of state investment incentives (e.g. tax/duty-free privileges). All five firms are vertically integrated with sugarcane farms. Their farm productivity ranges from 50 to 75 metric tons cane per hectare, or an average yield of 58 tons per hectare. Only three firms are practicing organic farming. Three firms adopted the costly modern muscovado process technology (e.g. boiler and steam jacketed kettles) while the two others chose the traditional open pan technology. Together they can produce up to almost 9 metric tons of muscovado per day. The firms have directly employed about 138 people in the mills. Muscovado powder is their main and common product, although the lead firm has diversified into other products (e.g. cube sugar and vinegar). Only this firm is catering to both domestic and export markets. It joins three other firms in serving the local market. A Five Forces Analysis gave these results : low threat of entry (due to such barriers as high initial investment cost); low to moderate bargaining power of supplier (main reason : mills have assured access to sugarcane); moderate rivarly (e.g. family ties and friendships temper competition); moderate to high bargaining power of buyers (e.g. foreign buyers require high volume but strictly demand quality); moderate to high threat of substitutes (e.g. raw and refined sugar are more affordable to consumers). A composite value chain map of the industry clothes includes the following upstream suppliers : a nursery operator, sugarcane farms (most with own trucks), private haulers, fertilizer traders, organic fertilizer manufacturers and lime producers. The downstream firms include bakeries, home-based secondary processors, foreign trading and import firms, a market agent, a local distributor, malls and other domestic/local retail outlets. Service providers include various government agencies, local government units, non-government organizations and utilities. Initial cluster mapping has graphically organized the potential cluster members, including the muscovado manufacturers, the sugarcane farms, their respective supporting suppliers or industries, the related industries, government agencies and other regulatory bodies, and assorted institutions providing education, research, training, financing, marketing and other services. Analysis of cluster-level determinants of competitive advantage tends to create a quite positive picture for the industry. The needed factors are mostly in place, except for certain specialized factors (e.g. R&D facilities). The home demand conditions, though not generally conducive, contain the potential for internationalization of local demand (e.g. via mobile foreign residents). Related and supporting industries (e.g. bakeries and coffee producers) are available but are mostly untapped and also in need of development. The context for film structure, strategy and rivalry is generally favorable, especially for corporate-type ventures. From all the foregoing indications, one may conclude that the local muscovado industy is consolidating its position in the domestic market but might yet expand with the entry of even micro enterprises and established sugar centrals. And though the industry is still unorganized, personal relationships can facilitate a clustering initiative. The industry, therefore, has adequate cluster potential. In view of the fairly positive assessment, it is recommended that a technical working group to study the clustering option be formed, among other actions. The DOST 7 should take the initiative in this regard and integrate the clustering approach in its development strategies and mechanisms. The LGUs, as stakeholders, should also adopt clustering as a local economic development strategy and formulate the appropriate policies, plans and programs.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Sugarcane industry -- Philippines; Sugarcane -- Philippines; Muscovado industry .